Clinical practice guidelines for the diagnosis and management of atopic dermatitis - Kanokvalai Kulthanan (2022)
Atopic dermatitis (AD), a chronic, relapsing dermatitis, is characterized by dry and pruritus skin in patients with a personal or family history of atopy. It affects up to 20% of children and 1-3% of adults in most countries worldwide, and leads to significant treatment costs and morbidity. These guidelines are developed in accordance with evidence-based publications and expert opinions. Following simple algorithms, the guidelines aim to assist adult and pediatric physicians in the better care of patients with AD. As with other diseases, there have been several diagnosis criteria proposed over time. Nonetheless, the classical Hanifin and Rajka criterion with no pathognomonic laboratory biomarkers is still the most widely used worldwide for the diagnosis of AD. The management of AD must be considered case by case to provide suitable care for each patient. Basic therapy is focused on avoiding specific/unspecific provoking factors and hydrating skin. Topical anti-inflammatory treatments such as glucocorticoids and calcineurin inhibitors are suggested for disease flare, and proactive therapy is best for long-term control. Other therapies, including antimicrobial agents, systemic antihistamines, systemic anti-inflammatory agents, immunotherapy, phototherapy, and psychotherapy, are reviewed in these guidelines. Crisaborole, a new topical phosphodiesterase 4 inhibitor, can be used twice daily in AD patients over three months old. Dupilumab, a biological drug for patients with moderate-to-severe AD, may be considered in patients with no improvement from other systemic treatments.